2021
DOI: 10.3389/fpsyg.2021.732605
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Creativity of Chinese Upper-Secondary-School Students Participating in Programming Education

Abstract: Purpose: This study explored whether instructional characteristics, learner characteristics, family socioeconomic status, and gender influence creativity in the context of programming education in China.Methods: A total of 851 upper-secondary-school students in Beijing, China, were surveyed using the Creativity Scale, Programming Learning Scale, Programming Teaching Scale and Family Socioeconomic Status Questionnaire. SPSS (version 22) was used for correlation analysis, t-test and regression analysis.Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 77 publications
1
0
0
Order By: Relevance
“…As factors related to innovation ability, male students tend to get higher score in creative thinking, academic performance and performed better for scienti c innovation ability, which is consistent with the results of some studies [24,25], but not with some others [26][27][28][29]. It may be argued that gender differences in creativity may originate from cultural and social factors, and some misconceptions such as "men are more intelligent and that women should make more efforts to succeed" may exaggerate gender differences.…”
Section: Discussionsupporting
confidence: 89%
“…As factors related to innovation ability, male students tend to get higher score in creative thinking, academic performance and performed better for scienti c innovation ability, which is consistent with the results of some studies [24,25], but not with some others [26][27][28][29]. It may be argued that gender differences in creativity may originate from cultural and social factors, and some misconceptions such as "men are more intelligent and that women should make more efforts to succeed" may exaggerate gender differences.…”
Section: Discussionsupporting
confidence: 89%
“…According to previous study both the teacher's and the students' abilities to create and complete projects have an impact on PjBL's effectiveness (Cintang et al, 2018). In addition, the development of creative thinking skills is also influenced by cognitive abilities (Frith et al, 2020;Liu et al, 2021). A study in high school students, showed that students with high academic abilities had higher scores in creative thinking skills compared to students with low academic abilities (Santi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These skills will be developed in line with the opportunities given to each learning activity (Kim, 2019;Wahyudi & Winanto, 2018). Several studies have proven that project-based learning and inquiry can improve creative thinking skills (Liu et al, 2021;Santi et al, 2018;Yamin et al, 2020). Some research done earlier showed that project-based science learning improves creative thinking skills significantly (Nuswowati & Taufiq, 2015;Ummah et al, 2019;Yamin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%